2018
DOI: 10.1002/cm.21427
|View full text |Cite
|
Sign up to set email alerts
|

Intraflagellar transporter protein 140 (IFT140), a component of IFT‐A complex, is essential for male fertility and spermiogenesis in mice

Abstract: Intraflagellar transport (IFT) is a conserved mechanism essential for the assembly and maintenance of most eukaryotic cilia and flagella. However, little is known about its role in sperm flagella formation and male fertility. IFT140 is a component of IFT-A complex. In mouse, it is highly expressed in the testis. Ift140 gene was inactivated specifically in mouse spermatocytes/spermatids. The mutant mice did not show any gross abnormalities, but all were infertile and associated with significantly reduced sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…However, variants affecting other constituents of the intraflagellar transport complex A have been shown to compromise male reproduction. Mice with a loss-of-function variant in the IFT140 gene show multiple morphological aberrations of the sperm including short and/or bent sperm tail and abnormal heads [77]. Compound heterozygosity in human IFT140 is associated with reduced sperm count and an excess of sperm with head and tail anomalies in an otherwise healthy individual [78].…”
Section: Discussionmentioning
confidence: 99%
“…However, variants affecting other constituents of the intraflagellar transport complex A have been shown to compromise male reproduction. Mice with a loss-of-function variant in the IFT140 gene show multiple morphological aberrations of the sperm including short and/or bent sperm tail and abnormal heads [77]. Compound heterozygosity in human IFT140 is associated with reduced sperm count and an excess of sperm with head and tail anomalies in an otherwise healthy individual [78].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis through the Mutation Taster database predicted a high probability of damage‐causing by both variations, while Polyphen‐2, SIFT, and SNPs&GO analyses suggested that both variations were neutral. However, a recent animal study (Zhang et al, ) found that IFT140 was a key regulator of male fertility and normal spermatogenesis in mice. Ift140 was highly expressed in the testicular tissues of normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's spermatozoa displayed bulged flagellar tips, as observed in Ift140‐deficient mice. This is a typical phenotype of retrograde trafficking deficiency (Hirano, Katoh, & Nakayama, ; Zhang et al, ). As the patient displayed almost the same conditions with the male germ cell‐specific Ift140‐deficient mice, we assumed that the IFT140: Asp613Asn and IFT140: Ser1416Asn mutations disrupt key protein‐binding sites or secondary structures of IFT140, leading to attenuated protein function in the spermatogenesis, but not affecting its functions in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that some ciliopathies are associated with a higher prevalence of male infertility and that motile cilia components are essential to male fertility (Zhang et al ., , , ; Liu et al ., ), little is known regarding the involvement of primary cilia in the control of male reproductive function. Accumulating experimental evidence acquired from animal models or human tissues suggests the importance of primary cilia in reproductive tract development and homeostasis (Table ), both of which are essential to male fertility control .…”
Section: Primary Cilia and Male Reproductive Tract Dysfunctionsmentioning
confidence: 99%